LEGAL ASPECTS OF CONSUMER PROTECTION IN PROTECTING THE MENTAL HEALTH OF ONLINE GAME PLAYERS - Hansto Ruben Gusti Oscar (RADJA PUBLIKA, 2024)
Online games are a business commodity that is growing rapidly in society. The high interest in playing online games cannot be separated from the ease with which everyone can access various types of online games via the internet. The people's desire to play online games is only for entertainment, but unwise use can turn into a loss for the community. Online Games can cause addiction which damages the mental health of Online Game players. even though consumers in using goods have the right to security, comfort, and safety. Law number 8 of 1999 concerning Consumer Protection is a reference for every business actor in trading their products in the community. consumer rights must be fulfilled and guaranteed by business actors.